The city of God against the pagans - Augustine, Saint, Bishop of Hippo; Dyson, R. W (Cambridge ; New York : Cambridge University Press, 1998)
This is the first new rendition for a generation of The City of God, the first major intellectual achievement of Latin Christianity and one of the classic texts of Western civilisation. When he began to write The City of God in 413, St. Augustine's intention was to defend the Christian Church against the charge of having brought about the Sack of Rome in 410
Outgrowing this initial purpose, the work evolved into a detailed critique of the political and moral tradition of Rome and a synthesis of Platonism and Christianity which must stand as one of the most significant achievements in Western intellectual history. Apart from its intrinsic interest the Christian account of social and political relations which Augustine gives was to furnish one of the most fertile sources of material for the controversial literature of the middle ages. R.W
Dyson has produced a complete, accurate, authoritative and fluent translation of The City of God, edited together with full biographical notes, a concise introduction, bibliographical note and chronology of Augustine's life
Includes bibliographical references (p. xxxi-xxxiii) and index
Keywords: Kingdom of God -- Early works to 1800; Apologetics -- Early works to 1800